Anharmonic interstellar PAH molecules. Issue 2 (14th September 2016) - Candian, Alessandra; Mackie, Cameron J.
Abstract: Polycyclic aromatic hydrocarbon (PAH) molecules are responsible for a family of features, the aromatic infrared bands, which are observed in many astronomical environments. The photophysics and photochemistry of PAHs in space is strongly influenced by anharmonicity, which has seldom been considered in astrophysical modeling because of the lack of available data or because too computationally demanding. Recent developments of second‐order vibrational perturbation theory applied to density functional theory now allow the computation of the anharmonic quartic force field anharmonic spectra of medium‐large molecules like PAHs in a time‐efficient way. It is now possible to have a better grasp of the effects of anharmonicity on the vibrational spectrum of PAHs also thanks to the comparison with gas‐phase, high‐resolution experimental data. In this perspective, the quality of these anharmonic spectra for PAH molecules is reviewed and discussed in view of a robust astrochemical model for PAH molecules. Abstract : Polycyclic aromatic hydrocarbon (PAH) molecules are of great interest for astronomers as they are responsible for the aromatic infrared bands, found in many astrophysical environments. A detailed knowledge of PAH anharmonicity will permit use of them as probes of physical and chemical conditions in space. This perspective takes a look to the theoretical advance in the DFT anharmonic vibrational spectra for PAHs and discuss their potential and the current challenges.